The history of ancient Thrace, a field for methodological experimentation and epistemological reflection (Research Announcements "Heritage BG", 2025)
This paper investigates the possible benefits of challenging the traditional protohistorical approach to Ancient Thrace. The analysis of Greek myths featuring the Thracians, notwithstanding modern prejudice, illustrates the strong integration of the Ancient Thracians in Greek representations and history, underlining the stakes of including the Thracians into the grand historical narrative. The paper also briefly presents the methodologies that make Ancient Thrace a stimulating and potentially groundbreaking subject for historical study. References:Bayliss, Andrew J. (2014). ‘Artful dodging’, or the sidestepping of oaths. In Sommerstein Allan H., Torrance Isabelle C. (eds), Oaths and swearing in Greece, Berlin, Boston, 240-280.Goossens, Roger. (1932). La date du Rhesos. L’Antiquité classique 1. 1-2, 93-134.Picard, Olivier. (2000). Monnayages en Thrace à l’époque achéménide. In Casabonne Olivier (éd.), Mécanismes et Innovations Monétaires dans l’Anatolie Achéménide – Numismatique et Histoire – Actes de la Table Ronde Internationale d’Istanbul, 22-23 mai 1997, Varia Anatolica 7, De Boccard, Paris, 239-253.Rufin Solas, Aliénor. (2013). L’or et l’argent des aristocraties thraces. Contribution de l’étude des trésors contenant des vases en métal précieux à l’histoire de la région aux IVe et IIIe s. av. J.-C. In Rufin Solas Aliénor (ed.), Armées grecques et romaines dans le nord des Balkans. Conflits et intégration des communautés guerrières, Gdansk, 29-50.Rufin Solas, Aliénor. (2022). Anthropology of war exchanges: a new approach to premodern warrior societies without written literature. In Delev P., Stoyanov T., Yanakieva Sv., Popov Chr., Bozhkova A., Vassileva M., Tzvetkova J., Damyanov J., Ilieva P., Emilov J. (eds), Ancient Thrace: Myth and Reality. The Proceedings of the Thirteenth International Congress of Thracology, September 3-7 2017, Sofia, 297-302.Torrance, Isabelle C. (2012). Oaths and “the barbarian”. In Sommerstein Allan H., Torrance Isabelle C. (eds), Oaths and swearing in Greece, Berlin-Boston, 307-322.
Keywords: protohisrory; mythography; athens; alliances; precious metal objects; coins